2014
DOI: 10.1002/jhet.2170
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Phase Transfer Catalysts for the Synthesis of Chiral N‐Heterocycles viaAsymmetric Cascade Reactions

Abstract: The effectiveness of a series of chiral phase transfer catalysts in cascade reactions of active methylene compounds with 2‐cyanobenzaldehyde leading to chiral 3‐substituted isoindolinones and fused benzoindolizidinones has been investigated. High yields and moderate enantiomeric excesses (e.e.s) were achieved employing a chiral phase‐transfer catalyst derived from bifunctional urea–quinine. Moreover, an efficient process of heterochiral crystallization, performed on moderately enantioenriched compounds, led to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 57 publications
0
14
0
Order By: Relevance
“…[169] They also demonstrated that this strategy may be further extended to produce ent-436 and ent-437 by using 440 (Scheme 112) as ac hiral phase-transfer catalyst. [170] Enders and co-workers reported as tereoselective synthesiso fe nantioenriched tetrahydropyridines 442 with high yields and excellent stereoselectivities from the intermediates 441,which were formed via Michael addition reactions between nitroalkenes 76 and1 ,3-diketones 379,c atalyzed by aq uinine-derived squaramide 443 (Scheme 113). [171] Thei ntermediates 441 underwent ad omino aza-Henry/cyclization reaction with the pre-formed aldimines 444 to afford the final products 442.T he reactionm ay also be carried out by adding all three of the substratest ogether at the beginningoft he reaction.…”
Section: 211synthesis Of Aza-heterocyclesmentioning
confidence: 99%
“…[169] They also demonstrated that this strategy may be further extended to produce ent-436 and ent-437 by using 440 (Scheme 112) as ac hiral phase-transfer catalyst. [170] Enders and co-workers reported as tereoselective synthesiso fe nantioenriched tetrahydropyridines 442 with high yields and excellent stereoselectivities from the intermediates 441,which were formed via Michael addition reactions between nitroalkenes 76 and1 ,3-diketones 379,c atalyzed by aq uinine-derived squaramide 443 (Scheme 113). [171] Thei ntermediates 441 underwent ad omino aza-Henry/cyclization reaction with the pre-formed aldimines 444 to afford the final products 442.T he reactionm ay also be carried out by adding all three of the substratest ogether at the beginningoft he reaction.…”
Section: 211synthesis Of Aza-heterocyclesmentioning
confidence: 99%
“…However,t he preparation of the aforementioned starting materials 73 required al ong synthetic pathway.C ascade reactions were naturally taken into account to overcome this shortcoming. In 2015, [39] Massa and co-workersr eporteda ne fficient cascade reactiono f2 -cyanobenzaldehyde 75 with active methylene compounds 76,r esulting in chiral products 77,w hich furtherr eacted with acrylaldehyde to form fused products 78 (Scheme 18). Various catalysts have been investigated and PTC-3,b earing an urea-quinine bifunctional group, was an appropriate choice.…”
Section: Phase Transfer Catalyzed Asymmetric Synthesis Of Isoindolinonesmentioning
confidence: 99%
“…Normally, three‐component reactions of 112 a , amine, and a nucleophile produce isoindolinones, but similar reactions with 2‐cyanobenzaldehyde tended to give isoindolin‐1‐imine derivatives in some cases . 2‐Substituted 3‐alkoxyisoindolin‐1‐imine derivatives could be obtained through the three‐component condensation of 2‐cyanobenzaldehyde, amine, and alcohol . Synthetic reactions of 3‐substituted isoindolinones from 2‐cyanobenzaldehyde have also been derivatized into an asymmetrical version with the aid of a phase‐transfer catalyst derived from bifunctional urea–quinine …”
Section: Benzaldo‐x Bifunctional Building Blocks and Their Heterocyclmentioning
confidence: 99%